APPLYING AN INTEGRATED ROUTE OPTIMIZATION METHOD AS A SOLUTION TO THE PROBLEM OF WASTE COLLECTION - Salleh, Abdul Hakim; S. Ahamad, Mohd Sanusi; Yusoff, Mohd Suffian (Copernicus Publications, 2016)
Solid waste management (SWM) is very subjective to budget control where the utmost expenses are devoted to the waste collection’s travel route. The common understanding of the travel route in SWM is that shorter route is cheaper. However, in reality it is not necessarily true as the SWM compactor truck is affected by various aspects which leads to higher fuel consumption. Thus, this ongoing research introduces a solution to the problem using multiple criteria route optimization process integrated with AHP/GIS as its main analysis tools. With the criteria obtained from the idea that leads to higher fuel consumption based on road factors, road networks and human factors. The weightage of criteria is obtained from the combination of AHP with the distance of multiple shortest routes obtained from GIS. A solution of most optimum routes is achievable and comparative analysis with the currently used route by the SWM compactor truck can be compared. It is expected that the decision model will be able to solve the global and local travel route problem in MSW.